The Influence of Service Quality, Price, and Promotion on Customer Satisfaction: A Study on Shopee E-Commerce Users in the Sugio Region - Devy Ayu Zulia Fitri; Nurul Badriyah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the influence of service quality, price, and promotion on customer satisfaction in the context of Shopee e-commerce users in the Sugio region. Employing a quantitative descriptive approach with a case study design, primary data were collected from 100 respondents using structured questionnaires distributed online. The data were analyzed using SPSS version 26 through multiple linear regression, t-test, F-test, and coefficient of determination (R²). The findings reveal that price and promotion have a significant and positive influence on customer satisfaction, while service quality does not show a significant effect. Among the variables, price emerged as the most dominant factor, suggesting that customers in Sugio are more price-sensitive in their online purchasing decisions. The study concludes that implementing competitive pricing and engaging promotional strategies are crucial to enhancing customer satisfaction on e-commerce platforms, particularly in semi-rural markets.